The effects of high-intensity interval training on cognitive performance: a systematic review and meta-analysis - Kaihang Liu; Wei Zhao; Congcong Li; Ying Tian; Lijuan Wang; Jingyi Zhong; Xu Yan; Yezheng Wang; Liyan Wang; Hongbiao Wang (Scientific Reports)
Abstract Cognitive decline is an important feature of an aging population. Despite the large body of research investigating the effects of high-intensity interval training (HIIT) on cognitive performance, reports of its effectiveness are inconsistent and it is difficult to determine what factors moderate these effects. The purpose of this study was to conduct a meta-analysis of existing randomised controlled trials investigating the effects of HIIT on various domains of cognitive performance, and to further examine the intervention cycle and age-related moderating effects. A comprehensive literature search was conducted across a range of databases, including PubMed, Embase, the Cochrane Library, Web of Science, Scopus, and EBSCO. The meta-analysis included data from 20 RCT studies. The results of the analyses demonstrated that HIIT significantly enhanced information processing (SMD = 0.33, 95% CI: 0.15–0.52, P = 0.0005), executive function (SMD = 0.38, 95% CI: 0.26 – 0.50, P < 0.00001), and memory (SMD = 0.21, 95% CI: 0.07–0.35, P = 0.004). Subgroup analyses demonstrated that HIIT enhanced information processing in individuals aged 60 and above, improved executive functioning in individuals of all ages, and enhanced memory in individuals aged 30 to 60. Acute HIIT improved executive function, less than 8 weeks of HIIT improved executive function and memory, and more than 8 weeks of HIIT improved information processing, executive function and memory. The findings of this study indicate that HIIT has a beneficial effect on cognitive performance. Chronic HIIT represents a potential non-pharmacological intervention for cognitive health. Further high-quality research is required to validate and extend these findings.